BORROWINGS FROM THE ENGLISH LANGUAGE IN RUSSIAN-LANGUAGE WEBSITES IN THE ASPECT OF INTERCULTURAL COMMUNICATION - Kadirniyazova, Aynura Kurbaniyazovna; Kabulova , Lola Tolibayevna (Educational Research in Universal Sciences, 2023)
At the contemporary stagecoach of evolution, communication occupies an far-reaching accommodation in the expenditure transaction of whatever In the circumstance of globalization, there is a collaboration between contradistinctive nation in the grassland of body of knowledge economics, political science culture, which show the way to substantial substitution in governmental parlance and communication is not a unchanging quantity; it is enterprising and proficient of development. The justification for the substantial pre-eminence of the English language fronting the qualifications of other languages and its growing consequence on other linguistic sophistication are investigated. outstanding to the impossibleness of nation to safeguard themselves from such an English-language introduction, the publication of preserving the governmental language, its features, cultural values and national identity comes to the fore. A variant of global bilingualism or multilingualism is advised as a way to solve rising linguistic and cultural problems. Learning a foreign language is not difficult for a modern person, it is advised a variant of the norm and is welcomed in existing living conditions. The assumptions of modern Russian and foreign linguists about the prospects for the development and diffusive of English in the global language space are given. The article focuses on the influence of English linguistic culture on the Russian linguistic and cultural space, make an analogy with the mentality of the English-speaking and Russian-speaking peoples, and identifies the cocksureness and negative phenomena of this influence.